THE EVALUATION OF DIFFERENT THERAPIES IN THE PATIENTS WITH HELICOBACTER PYLORI - Ali ÖZDEN; Ömer DÖNDERİCİ; Şükrü DUMLU; F. IŞITAN; Hülya ÇETİNKAYA; Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-